ANALISIS PERLINDUNGAN HUKUM ATAS PENGHAPUSAN MEREK SECARA SEPIHAK OLEH DIREKTORAT JENDERAL KEKAYAAN INTELEKTUAL (Contoh Kasus: Putusan Nomor: 575 K/Pdt.Sus-HKI/2020) - Theresia Wijaya; Ariawan Gunadi (Jurnal Hukum Adigama, 2020)
Mark registration in Indonesia is carried out on the basis of the first to file principle which ensures that the first registrant is the legal owner of a Mark who has executive rights over a Mark. However, the development of the world of commerce encourages people to register their trademarks. And in the process, Double Registration often occurs. This thesis discusses the Trademark dispute between Ruben Onsu and Benny Sujono. This Mark Dispute will look at the fact which party is the first registrant, thus Marks which have similarities in essence will be canceled as contained in Decision number: 575 K / Pdt.Sus-HKI / 2020. In the dispute, a new problem arose in which Benny Sujono's Mark, which was the first registered and legal mark, was deleted under the argument of Article 72 of the Law on Trademarks and Geographical Indications as well as disturbing peace in society. Referring to the problem, the author uses normative legal research methods and the results of the research show that the negligence and subjectivity of the examiner are factors that cause double registration in trademark registration. And the elimination of a mark by the Directorate General of Intellectual Property cannot be done because there are no elements that are violated from Article 72 of the Trademark and Geographical Indication Law. Thus, it is concluded that the deletion of the Mark is inappropriate. On this basis, the author recommends taking legal remedies by filing a lawsuit at the State Administrative Court